Radiological risk from activity concentrations of natural radionuclides: Cumulative Hazard Index - Akozcan, Serpil; Kulahci, Fatih; Gunay, Osman; Ozden, Selin (Springer, 2021)
The Cumulative Hazard Index method has been proposed for the first time to determine the low and high-risk levels of radionuclides. The significant radiological parameters and risk analyses for Ra-226, Th-232 and K-40 pollution levels control in the soil are determined through the probability distribution functions. The activity concentration of Ra-226, Th-232 and K-40 in samples were found to vary from of 16 +/- 0.6 to 62 +/- 3.2 Bq kg(-1) with an average 30 +/- 1.1 Bq kg(-1), 24 +/- 0.9 to 63 +/- 1.3 Bq kg(-1) with an average 37 +/- 1.0 Bq kg(-1) and 316 +/- 5.8 to 878 +/- 6.9 Bq kg(-1) with an average 525 +/- 6.2 Bq kg(-1), respectively.
Keywords: Transport; Risk analysis; Cumulative hazard; Radiation hazards; Soil